A channel visiting strategy based on joint optimization of probability of handoff failure and capacity of secondary user - Mengdi XU; Ming JIN; Jingwen TONG (Dianxin kexue)
The available channel visiting strategy for spectrum handoff mainly considers the probability of handoff failure more than the channel capacity.Aiming at the problem,anovel spectrum suitching channel visiting strategy was proposed based on the probability of handoff failure and the channel capacity foins optimixing of secondary user.It was proved that the maximum channel capacity of secondary user can be obtained by visiting the channel in the descending order of the signal to noise ratio(SNR),and the minimum probability of handoff failure couldbe obtained in the descending order of the mean vacant time duration.Then the mean vacant time of channel and SNR for sorting and weighted combination was processed of non-parameterization.At last,the channel was visited in descending order according to the result of non parametric processing.The numerical results show that the proposed method can increase the channel capacity of secondary user by about 50%,while keeping the probability of handoff failure close to the minimum.